Shelf life extension of wheat bread by alhydwan flour and Carboxymethylcellulose and improvement of their quality characteristics, dough rheological and microstructure - Ammar Al-Farga; Siddeeg Azhari; Aqlan Faisal M.; Howladar Saad M.; Refai Mohammed Y.; Afifi Mohamed; Ali Haytham A.; Hajjar Dina; Sulamain Mohamed G.M.; Chamba Moses V.M.; Kimani Bernard Gitura; Saleh Anwar; et al. (2020)
Alhydwan, has been used in bakery products for many years in South of Yemen. Alhydwan primary function in bakery products is to inhibit moisture content during storage, leading to improved shelf life. However, as a fresh strategy to bread staling, no extensive study has been conducted to evaluate its potential. The present study therefore examined the alhydwan as a comparison with Carboxymethylcellulose (CMC) at 0.5% (w/w) level in dough rheology improvement, microstructure, quality parameters and delayed wheat bread staling. The CMC or alhydwan for farinograph characteristics comprising the dough's portrayed showed greater water absorption, while growth and stability time was significantly decreased. Staling of bread, the findings showed that in both alhydwan and CMC minimized crumb hardening frequency and enhanced freshness, quality and retention ability for moisture, making the bread softer and postponed staling. The microstructure of CMC or alhydwan supplemented formulation showed the distinguishable characteristics and constituents that could explain, to some degree, that the CMC and alhydwan had antistaling effect. The incorporation of alhydwan such as CMC into the formulation of bread could thus play a sustainable role in improving the quality of bread by having an extended shelf life. © 2020 Elsevier B.V.